PENGARUH EDUKASI BUKU SAKU TERHADAP PERILAKU ASUPAN ZAT BESI IBU HAMIL TERKAIT PENCEGAHAN ANEMIA DEFISIENSI BESI (Studi pada Ibu Hamil Trimester II Akhir di Wilayah Kerja Puskesmas Bangetayu Kota Semarang) - Aqilatul Munawaroh; Sri Achadi Nugraheni; M. Zen Rahfiluddin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Iron deficiency anemia is one of the most risky nutritional problems suffered by pregnant women. Anemia in pregnancy affects the increased risk of maternal mortality, prematurity, low birth weight and infant mortality, so efforts are needed to improve anemia prevention behavior in pregnant women. The purpose of this study was to determine the effect of nutrition education using pocket book on iron intake behavior in pregnant women. The behavioral domain under study consisted of knowledge, attitudes, the level of iron adequacy and the level of adherence to the consumption of additional blood tablets in pregnant women. The method in this study is Quasy Experimental with the design of one group pre-post test. Instruments for collected data consisted of a questionnaire and a 24-hour nutrient consumption recall form. Sampling of 45 pregnant women using purposive sampling technique according to inclusion criteria. Data were tested for normality using Shapiro Wilk. Data analysis used Paired T-test and Wilcoxon Signed Ranks Test. Different test results showed differences in conditions between before and after education on the knowledge variable (p<0,05), attitude (p<0,05), iron adequacy level (p<0,05) and the level of adherence to the consumption of added tablets (p<0,05). The results of study showed an increase in the knowledge score of 3,7; the attitude score increased by 3,4; the iron adequacy level increased by 12,9% and the increase in the level of adherence to the consumption of additional blood tablets by 12,4%. The conclusion of this study is that there are effects of pocket book education at knowledge, attitudes, the level of iron adequacy and the level of adherence to the consumption of additional blood tablets in pregnant women. Suggestion from this study is that pregnant women should pay more attention to the need for iron intake during pregnancy to avoid the risk of iron deficiency anemia.